Identification of CD14 and lipopolysaccharide-binding protein as novel biomarkers for sarcoidosis using proteomics of serum extracellular vesicles. (16th March 2022) - Futami, Yu; Takeda, Yoshito; Koba, Taro; Narumi, Ryohei; Nojima, Yosui; Ito, Mari; Nakayama, Mana; Ishida, Mimiko; Yoshimura, Hanako; Naito, Yujiro; Fukushima, Kiyoharu; Takimoto, Takayuki; et al.
Abstract: Sarcoidosis is a complex, polygenic, inflammatory granulomatous multi-organ disease of unknown cause. The granulomatous inflammation in sarcoidosis is driven by the interplay between T cells and macrophages. Extracellular vesicles (EVs) play important roles in intercellular communication. We subjected serum EVs, isolated by size exclusion chromatography, from seven patients with sarcoidosis and five control subjects to non-targeted proteomics analysis. Non-targeted, label-free proteomics analysis detected 2292 proteins in serum EVs; 42 proteins were up-regulated in patients with sarcoidosis relative to control subjects; and 324 proteins were down-regulated. The protein signature of EVs from patients with sarcoidosis reflected disease characteristics such as antigen presentation and immunological disease. Candidate biomarkers were further verified by targeted proteomics analysis (selected reaction monitoring) in 46 patients and 10 control subjects. Notably, CD14 and lipopolysaccharide-binding protein (LBP) were validated by targeted proteomics analysis. Up-regulation of these proteins was further confirmed by immunoblotting, and their expression was strongly increased in macrophages of lung granulomatous lesions. Consistent with these findings, CD14 levels were increased in lipopolysaccharide-stimulated macrophages during multinucleation, concomitant with increased levels of CD14 and LBP in EVs. The area under the curve values of CD14 and LBP were 0.81 and 0.84, respectively, and further increased to 0.98 in combination with angiotensin-converting enzyme and soluble interleukin-2 receptor. These findings suggest that CD14 and LBP in serum EVs, which are associated with granulomatous pathogenesis, can improve the diagnostic accuracy in patients with sarcoidosis. Abstract : Proteomics of extracellular vesicles reveals new sarcoidosis biomarkers Graphical Abstract: